Phenotyping of Staphylococcus aureus reveals a new virulent ST398 lineage. (23rd February 2012) - Schmidt, T.; Zündorf, J.; Grüger, T.; Brandenburg, K.; Reiners, A.‐L.; Zinserling, J.; Witte, W.; Schnitzler, N.
<x xml:space="preserve">Abstract</x> Clin Microbiol Infect 2013; 19: 279–285 Abstract Staphylococcus aureus sequence type (ST)398, which is commonly found as a colonization strain in pig farming, is emerging more frequently as the cause of human infections. In this study, we analysed ST398 of porcine and human origin at the genetic, protein and immunogenic levels. Although genetic analysis of the genes encoding the major virulence factors revealed the presence of the same genes in all strains studied, the results demonstrated spa type crossing alterations in adhesion abilities in addition to a strongly enhanced lysis activity directly linked to impaired clearance attributable to polymorphonuclear leukocytes (PMNs). This change in virulence pattern indicates high heterogenicity in the ST398 pool that is not based on a different genetic make‐up, but probably on variations in the genetic regulation systems. These modifications, which are tightly connected to pathogenicity, cannot be detected by conventional diagnostic methods.